A literature review of motivation theories - Doğan, Yunus; Cebecik, Enes; Özdemir, Emine Ören (Nova Science Publishers, Inc., 2024)
This chapter dwells upon motivation concept and theories of motivation. With the industrialization and the monotony of jobs, it has been noted that job satisfaction has decreased and there is an increased interest in studying human behavior. Motivation has been identified as an important source that influences individuals' behavior. Motivation is defined as the force that manages individuals' desires, goals, needs, and aspirations. Intrinsic motivation is described as the willingness of an individual to engage in a task due to internal factors. External motivation, on the other hand, is when an individual is motivated to work for a goal or reward due to external factors. The process of motivation involves the identification of needs, arousal, behavior guidance, and achieving desired outcomes. It is important to accurately identify needs and encourage desired behaviors for this process to be effective. Motivation is a concept that aims to understand the reasons behind human behavior. Motivation is influenced by factors such as individuals' needs, desires, and goals, and these factors explain how individuals' behavior can be changed. Motivation plays a significant role in human life and helps us understand people's behaviors. Understanding motivation and developing effective motivational strategies based on this knowledge can assist individuals in achieving success. Therefore, it is important to continue with motivation studies and research. Motivation theories are research efforts aimed at understanding the reasons behind human behavior and how these behaviors can be changed. These theories explain how factors such as individuals' needs, desires, and goals influence behavior. In this article, we have examined different motivation theories and investigated which ones are more effective in specific situations. As a result, motivation theories are important tools for understanding and changing human behavior, and by considering these theories, we can develop more effective motivational strategies. When looking at motivation theories, it can be observed that these theories generally do not contradict each other. Most theories attempt to complement the shortcomings of previous theories or draw attention to factors that other theories may have overlooked. In this context, it is understood that in order to understand the concept of motivation, each of these theories should be taken into account. In order to comprehend the concept of motivation in individuals, it is necessary to consider all motivational factors by taking into account the individual's intrinsic and extrinsic sources of motivation. Considering that individuals are influenced by motivational factors at different levels, we can say that the motivation level and direction of each individual will yield different results in different factors. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Motivation; Motivation process; Motivation theories; Types of motivation